Development of services in the field of research data management and scholarly communication at the University of Vienna - Blumesberger, Susanne; Ganguly, Raman (Septentrio Conference Series, 2020)
In 2008 the University of Vienna released the institutional repository PHAIDRA. With this release, several services for research data management followed soon. It is still essential to review the services and integrate new one, related to the change of the research practice. The demand for training and support is increasing, and more often, we see now the need for consulting services. That service supports the research cycle from writing a data management plan to getting DOIs for data and are integrated into the PHAIDRA portfolio. PHAIDRA is a cooperation between the Central University Computer Center and the University Library for researcher and research projects of the University of Vienna. To be alleged with the actual changes in research data management, PHAIDRA regularly participates in national and international projects, like Austrian Data Lab and Services and FAIR Data Austria nationally as well as implementing with COAR (Confederation of Open Access Repositories) a vocabulary service and engaging with researcher projects together with RDA (Research Data Alliance) internationally. Several networks such as the network for repository managers (RepManNet) or the network for sustainable software development (code4research), and the network of other PHAIDRA users at other universities in Austria, Italy and Balkan countries, enable constructive cooperation on a technical, library and scientific level on various topics. The poster intends to give an insight into these activities.